When experts agree using non-affiliated experts to rank popular topics. - Bharat, Krishna; Mihaila, George A.
In response to a query, a search engine returns a ranked list of documents. If the query is about a popular topic (i.e., it matches many documents), then the returned list is usually too long to view fully. Studies show that users usually look at only the top 10 to 20 results. However, we can exploit the fact that the best targets for popular topics are usually linked to by enthusiasts in the same domain. In this paper, we propose a novel ranking scheme for popular topics that places the most authoritative pages on the query topic at the top of the ranking. Our algorithm operates on a special index of "expert documents." These are a subset of the pages on the WWW identified as directories of links to non-affiliated sources on specific topics. Results are ranked based on the match between the query and relevant descriptive text for hyperlinks on expert pages pointing to a given result page. We present a prototype search engine that implements our ranking scheme and discuss its performance. With a relatively small (2.5 million page) expert index, our algorithm was able to perform comparably on popular queries with the best of the mainstream search engines.
Keywords: WWW search; Authorities; Connectivity; Host affiliation; Link analysis; Ranking; Topic experts